Phosphorus recovery from cattle manure bottom ash by extraction and precipitation methods - Yang, Heejin; Kang, Jin Kyu; Park, Seong Jik; Lee, Chang Gu (Environmental Science and Pollution Research, 2022)
Phosphorus, a limiting element, is essential for living organisms, but the total amount available is decreasing with its increasing use. This problem can be solved by studying the methods of phosphorus recovery from waste. Phosphorus (P2O5, 13.75%) is abundantly present in cattle manure bottom ash (CMBA), indicating its potential as a source for phosphorus recovery. Herein, phosphorus recovery from CMBA was investigated by acid extraction and precipitation methods. The optimum concentration of sulfuric acid for extraction was 1.4 M, which eluted approximately 90% of the phosphorus contained in CMBA. In the precipitation method, sodium hydroxide and calcium silicate hydrate (CSH, CaSiO3∙nH2O) were used to adjust the solution pH to 4 and 8, where more than 99% of the eluted phosphorus was recovered when the pH was adjusted to 8 using CSH alone. The chemical composition and crystal forms of the recovered precipitates were analyzed using X-ray fluorescence and an X-ray powder diffractometer. The results indicated monetite and brushite were the main crystal forms of precipitates at pH 4, and struvite, hydroxyapatite, and tricalcium phosphate were the main crystal forms at pH 8. The availability of phosphorus in the precipitates was also evaluated by quinoline gravimetric analysis using water and 2% citric acid, and the water-soluble precipitate was less than 35%, whereas it ranged from 65 to 97% in 2% citric acid. This study suggests that CMBA can be used as a promising source to recover phosphorus via acid extraction and precipitation processes.
Keywords: Animals; Cattle; Chemical Precipitation; Citric Acid; Coal Ash; Manure; Phosphates; Phosphorus; Struvite; Waste Disposal, Fluid; Water; Calcium silicate hydrate; Cattle manure bottom ash; Phosphorus; Precipitation; Recovery; Solution pH